The Effect of some inducer agents in increase the production of Enterocin U36 produced by Enterococcus faecalis U36 that isolated from Urinary Tract Infection (Baghdad Science Journal, 2025)
Enterocin U36 (ENT U36), is a bacteriocin produced by Enterococcus faecalis U36 , strain isolated from urine samples have collected from patients suffering from urinary tract infections . The Bacteriocin is an antimicrobial proteins or peptides that inhibit growth of bacteria closely related to the producing organism. The results has been shown that ENT U36 active against Enterococcus faecalis S10 Lactococcus lactis ,Lactobacillus fermentum and few other gram positive pathogens bacteria including Listeria monocytogenes, Staphylococcus auraus ,Bacillus subtilis and Streptococcus spp. The optimum conditions for enterocin production from selective local isolates EFU36 were determined by using the cultural submerged and the results showed that the optimum media for production of enterocin contained carbon sources , nitrogen source and some mineral salts with an inoculum size of 2% which contains 1x109 cell/ml. at an optimum pH 6 in optimum degree(35-37) in shaker incubator 120 cycle/ min reached to the specific activity of 91x103 unit/mg.The effect of some inducers of production like chloramphenicol, folic acid, vitamin B12 and mitomycin-c was studied. The results showed that 1.5% of mitomycin gave specific activity of about 103x103 unit/mg when added to the optimum media after 3 hours from optimum production period.